Can infected pancreatic necrosis really be managed conservatively?. Issue 11 (November 2018) - Al-Sarireh, Bilal; Mowbray, Nicholas G.; Al-Sarira, Ali; Griffith, David; Brown, Timothy H.; Wells, Toby
Abstract : Objectives: Guidelines advocate minimally invasive drainage rather than open surgery for infected pancreatic necrosis (IPN) after acute pancreatitis. We hypothesized that the conservative approach could be extended even further by treating patients using an antibiotics-only protocol. Patients and methods: Between June 2009 and July 2017, patients with IPN were selectively managed with carbapenem antibiotics for a minimum of 6 weeks. We compared these patients with patients who underwent minimal access retroperitoneal pancreatic necrosectomy (MARPN) for IPN to identify characteristics of this patient group. Results: Of 33 patients with radiologically proven IPN, 13 patients received antibiotics without any surgical or radiological intervention and resulted in no disease-specific mortality and one case of pancreatic insufficiency. In comparison, 44 patients underwent MARPN with a mortality of 20%, and 81.8% developed pancreatic insufficiency. The modified Glasgow score and computed tomography severity score was less in the antibiotic-only group ( P <0.001 and P =0.014, respectively). Patients who underwent MARPN had lower serum haemoglobin and albumin levels ( P =0.030 and 0.001, respectively), and a higher C-reactive protein ( P =0.027). Conclusion: Conservative treatment of IPN with antibiotics is a valid management option for haemodynamically stable patients experiencing less severe disease, requiring careful selection by experienced clinicians.